Analysis of the electron-stream effect in patients treated with partial breast irradiation using the 1.5 T MR-linear accelerator. (March 2021) - De-Colle, C.; Nachbar, M.; Mӧnnich, D.; Boeke, S.; Gani, C.; Weidner, N.; Heinrich, V.; Winter, J.; Tsitsekidis, S.; Dohm, O.; Zips, D.; Thorwarth, D.
Highlights: The electron-stream effect is responsible of an out-of-field dose when performing partial breast irradiation at the MR-linac. The electron-stream effect is located to the patient́s chin and, for lateral targets, to the arm. The electron-stream effect is effectively minimized by a bolus. Novel concepts and clinical trials for breast cancer at the 1.5 T MR-linac can be tested. Abstract: Introduction: The hybrid magnetic resonance linear accelerator (MRL) has the potential to test novel concepts in breast cancer patients such as daily MR-guided real-time plan adaptation. Before starting clinical trials, preparatory studies for example of the MR-dependent electron stream effect (ESE) are necessary. Material and Methods: To prospectively investigate the ESE, data from 11 patients treated with partial breast irradiation (PBI) at the 1.5 T MRL were evaluated. A bolus was placed on the chin and in vivo dosimetry results were compared with the dose simulated by the treatment planning system (TPS). The same measurements were carried out for three patients treated at a conventional linac. Toxicity and cosmesis were evaluated. Results: Median doses measured and simulated on top/ underneath the bolus were 1.91 / 0.62 Gy and 2.82 / 0.63 Gy, respectively. Median differences between calculations and measurements were 0.8 Gy and 0.1 Gy. At the conventional linac, median measured doses on top/ underneath the bolus were 0.98 and 1.37 Gy. No acute toxicity exceeding grade 2 was recorded. Cosmesis was good or excellent and patient reported outcome measures were mostly scored as none or mild. Conclusion: The dose due to the ESE is low, correctly predicted by the TPS and effectively minimized by a bolus.